A case of aortopulmonary window mimicking common arterial trunk on fetal echocardiography - Wiecheć, Marcin; Nocuń, Agnieszka; Merta, Malwina; Januszewska, Katarzyna; Malec, Edward (Prenatal Cardiology, 2023)
Aortopulmonary window (APW) is a rare congenital cardiac anomaly characterised by abnormal communication between the aorta and the pulmonary trunk in the presence of separately formed semilunar valves. We present a case that was initially diagnosed in prenatal life at 21 weeks as common arterial trunk. Follow-up scans starting from 31 weeks revealed APW type I in the setting of tetralogy of Fallot (S, D, S) with a right-sided aortic arch with wide interatrial communication. The neonate was born at 38 weeks of gestation by caesarean section; its birth weight was 2825 g. The postnatal echocardiogram confirmed the prenatal diagnosis provided later in gestation. Three weeks after birth, the child was scheduled for surgery: complete repair and APW closure using an autologous pericardial patch, excision of trabeculae in the right ventricular outflow tract (RVOT), transannular reconstruction below the RVOT, reconstruction of the RVOT, and partial ASD closure. The child was discharged from the hospital, weighing 3300 g, with 97% saturation. APW may remain undiagnosed until adulthood. A late diagnosis may result in congestive heart failure and irreversible damage to the pulmonary vessels. Early detection of APW, preferably in the prenatal period, remains the key issue in terms of this condition.